Evaluación del calor específico promedio de cinco jugos de frutas de la Amazonía Peruana mediante calorimetría diferencial - Guerra Momulada, Claudia Lucero (2025)
The general objective of this thesis was: to evaluate the average specific heat of five fruit juices from the Peruvian Amazon by differential calorimetry, for which an equation was deduced where the average specific heat is directly proportional to the speed of energy transferred and inversely proportional to the product of the mass with the rate of change of temperature with respect to time. Five (5) fruit juices from the Peruvian Amazon were selected as a sample, which were: camu camu, passion fruit, cocona, papaya and aguaje. When applying the aforementioned model to the selected fruit juices, the average specific heat with respect to the temperature interval resulted in: 3914.98 J/(kg.°C) (from 20.2 °C to 80 °C), 3820.88 J/(kg.°C) (from 20.4 °C to 80 °C), 3715.29 J/(kg.°C) (from 23.5 °C hasta 80 °C), 3897.46 J/(kg.°C) (from 20.1 °C to 80 °C) and 3685.43 J/(kg.°C) (from 20 °C to 80 °C), respectively. Similarly, when applying the Choi and Okos equations in the same order and temperature interval, the average specific heat was: 3896.21 J/(kg.°C), 3860.01 J/(kg.°C), 3854.06 J/(kg.°C), 3805.14 J/(kg.°C) and 3780.38 J/(kg.°C). When comparing the results using the differential calorimetry model with the Choi and Okos equations, the following error percentages were obtained respectively: 0.482 %, 1.014 %, 3.601 %, 2.426 % and 2.512 %, so it is concluded that the general objective has been met and simultaneously the general hypothesis has been tested.